Recursos educativos abiertos como posibilitadores de pensamiento crítico en dos ambientes de aprendizaje (2017)
The present study developed from a qualitative approach, based on action research. Thus, it described the educational needs found in the language and mathematics learning environments in a group of secondary education. The starting point was to analyze how the incorporation of Open Educational Resources (OER) can set a benchmark of pedagogical value that promotes experiences and proposals to strengthen higher order thinking skills. For this purpose, the instruments used to collect the data were OER form; the class register book, the teacher?s journal, Likert survey and focal Group. Likewise, the research team used Bloom's digital taxonomy in the creation of learning objectives and the selection of technological tools associated with mental actions. In this way, techno-pedagogical designs were created and reflected about their implementation. Simultaneously, it observed teachers and students? role and technological mediation. In conclusion, the results suggested that OER as a mediating element improves the learning environments and favors the Development of critical thinking. This approach was useful to transform the pedagogical practice.